Use of Lung Resection and Voriconazole for Successful Treatment of Invasive Pulmonary Aspergillus ustus Infection - Azzola, A. (American Society for Microbiology, 2004)
Invasive pulmonary aspergillosis (IPA) is a common infection in neutropenic patients and is associated with high mortality. Aspergillus ustus is a species that has only rarely been implicated in human disease. All reported cases of IPA due to A. ustus have been fatal. Here, we describe a case of invasive pulmonary A. ustus infection successfully treated with lung resection and voriconazole. A 43-year-old man with acute myeloid leukemia underwent two courses of chemotherapy and experienced prolonged neutropenia. Treatment with amphotericin B was given for persistent fever. While he was receiving amphotericin B, a progressive opacity developed in the upper right lobe. Lung tissue obtained through pulmonary wedge resection for histology showed a mold with septate hyphae, consistent with IPA due to Aspergillus. A. ustus was grown in culture. The patient was then treated with voriconazole and remained in remission of the mold infection in spite of additional chemotherapy and a leukemic relapse. In summary, this report describes the successful treatment of invasive pulmonary A. ustus infection by lung resection and antifungal treatment with voriconazole in a neutropenic patient.